2014
DOI: 10.18632/oncotarget.2205
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone regulates adhesion, migration and matrix metalloproteinase 9 activity via αvβ3 integrin in myeloma cells

Abstract: Thyroid hormone (3,5,3′-triiodothyronine, T3; L-thyroxine, T4) enhances cancer cell proliferation, invasion and angiogenesis via a discrete receptor located near the RGD recognition site on αvβ3 integrin. Tetraiodothyroacetic acid (tetrac) and its nanoparticulate formulation interfere with binding of T3/T4 to the integrin. This integrin is overexpressed in multiple myeloma (MM) and other cancers. MM cells interact with αvβ3 integrin to support growth and invasion. Matrix metalloproteinases (MMPs) are a family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 49 publications
1
46
0
Order By: Relevance
“…The concentrations selected for T3 (1 nM) and T4 (100 nM) are slightly supraphysiological and physiological, respectively, as previously reported by our group in other experimental cancer models. [28][29][30] By using fluorescently dye-tagged T3 and T4, the membrane binding of the two hormones to OVCAR-3 cells (Figure 1b binding was scarcely detectable. Furthermore, an overnight incubation of OVCAR-3 cells with T3 or T4, induced clustering and abundance of the integrin on the cell surface by 2.5-fold and fourfold (quantified using NIH ImageJ software), respectively ( Figure 1c).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The concentrations selected for T3 (1 nM) and T4 (100 nM) are slightly supraphysiological and physiological, respectively, as previously reported by our group in other experimental cancer models. [28][29][30] By using fluorescently dye-tagged T3 and T4, the membrane binding of the two hormones to OVCAR-3 cells (Figure 1b binding was scarcely detectable. Furthermore, an overnight incubation of OVCAR-3 cells with T3 or T4, induced clustering and abundance of the integrin on the cell surface by 2.5-fold and fourfold (quantified using NIH ImageJ software), respectively ( Figure 1c).…”
Section: Resultsmentioning
confidence: 99%
“…62 This trafficking event was also shown to be ERK-dependent. 62 Given that the activation of ERK has been closely correlated with the thyroid hormonal action in cancer cells, 17,18,26,[28][29][30][63][64][65][66][67][68][69] together with the central role of MAPK in ovarian cancer, 70 led us to explore this pathway in our experimental system. Results in ovarian cancer cells similarly indicate activation of ERK by the hormones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Balzan et al (2013) reported similar effects on microvascular endothelial cells in a wound-healing assay with increased migration after T 3 or T 4 stimulation that was abolished by treatment with tetrac. Studies on multiple myeloma cells and bone marrow aspirates from multiple myeloma patients by Cohen et al (2014) illustrate thyroid hormone-dependent, avb3-mediated regulation of cell migration. Furthermore, there is growing evidence that thyroid hormones increase the motility of avb3-expressing immune cells, and, possibly by similar mechanisms, nerve cell migration (De Vito et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…BMSCs play crucial roles in MM progression and induction of drug resistance through cell-cell contact and secretion of cytokines [1, 145, 146]. MM cells adhere to BMSCs, stimulating the latter to secrete more soluble factors which mediate MM cell growth, survival, migration, drug resistance, and BM angiogenesis [145, 147151].…”
Section: Evs In MMmentioning
confidence: 99%